(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Marketing management of a higher education institution implies that after conducting marketing research, attention is focused on marketing strategy and marketing tactics. Strategic marketing includes market segmentation, targeting strategy selection and positioning. The bases for market segmentation can be diverse, and the aim is to identify segments and describe their profiles in such a manner that they are innerly homogeneous and mutually heterogeneous. The targeting strategy is about selecting the segments that the company will serve and choosing whether to implement it through a unique marketing mix or whether there will be differences in marketing mix instruments geared toward different segments. Positioning involves taking a place in the mind of the customer in a way that differentiates the company from the competition. These elements of the marketing strategy are applied in both the profit and non-profit sectors, including higher education institutions. The subject of this paper is the presentation of the segmentation of the enrollees of the higher education institution on the basis of enrollment motives, identification of their profiles, as well as making recommendations for targeting and positioning. In addition to the theoretical observation of these topics, a primary survey was conducted in 2019 on a sample of more than 400 respondents.